Frontispiece: Low‐Temperature Electrolyte Design for Lithium‐Ion Batteries: Prospect and Challenges. Issue 64 (17th November 2021) - Li, Qian; Liu, Gang; Cheng, Haoran; Sun, Qujiang; Zhang, Junli; Ming, Jun
Abstract : Lithium‐ion batteries have dominated the energy market from portable electronic devices to electric vehicles. However, the LIBs applications are limited seriously when they were operated in the cold regions and seasons if there is no thermal protection. This is because the Li + transportation capability within the electrode and particularly in the electrolyte dropped significantly due to the decreased electrolyte liquidity, leading to a sudden decline in performance and short cycle‐life. Thus, design a low‐temperature electrolyte becomes ever more important to enable the further applications of LIBs. Herein the low‐temperature electrolyte developments are summarized from the aspects of solvent, salt, additives, electrolyte analysis, and performance in the different battery systems. Recent new insights are also introduced about the cation solvation structure, which is significant to understand the interfacial behaviors at the low temperature, aiming to guide the design of a low‐temperature electrolyte more effectively. For more information, see the Review by J. Zhang, J. Ming et al. on page 15842 .